Studi Literatur : Analisis Kesesuaian Lahan Terhadap Lokasi Permukiman - Mella Febri Nurfikasari; Eppy Yuliani (Jurnal Kajian Ruang, 2022)
ABSTRACK          Settlement is one of the primary needed for humans. Settlement will increase every year, but the available land is relatively constant. In addition, there were uncorresponding in residential development that were not in accordance with the directions for spatial use. As a result, land use is less effective and maximal. Therefore, proper and optimal land use is needed so that increasing population growth can be fulfilled by the amount of land available. The purpose of this study is to analyze and assess the suitability of land for the development of suitable and targeted residential locations. This study used spatial analysis and descriptive empirical methods using analysis techniques such as scoring and overlay. Geographical Information System (GIS) is an analytical tool used in conducting land suitability research. The results of the research that have been carried out indicate that there are still settlements in several areas that are not in accordance with the direction of space utilization. This is the task of the government to make proper improvements and relocation in residential areas.Keywords: Spatial use, land suitability, settlement. ABSTRAK             Pemukiman merupakan salah satu kebutuhan primer bagi manusia. Kebutuhan pemukiman ini akan meningkat pada setiap tahunnya, akan tetapi lahan yang tersedia relatif tetap. Selain itu, terdapat kesalahan pembangunan pemukiman yang kurang sesuai dengan arahan pemanfaatan ruang. Akibatnya, pemanfaatan lahan kurang efektif dan maksimal. Oleh karena itu, dibutuhkan pemanfaatan lahan yang tepat dan optimal agar pertambahan penduduk yang semakin meningkat dapat terpenuhi dengan jumlah lahan yang ada. Tujuan pembuatan artikel ini untuk menganalisis serta mengkaji mengenai kesesuaian lahan terhadap pengembangan lokasi pemukiman yang sesuai dan  tepat sasaran. Artikel  ini menggunakkan metode analisis kualitatif dan deskriptif empiris. Berdasarkan hasil kajian literatur yang telah dilakukan menunjukkan bahwa masih terdapat pemukiman di beberapa daerah yang belum sesuai dengan arahan pemanfaatan ruang. Hal tersebut merupakan tugas pemerintah untuk melakukan pembenahan serta relokasi yang tepat pada kawasan pemukiman.Kata Kunci : Pemanfaatan ruang, kesesuaian lahan, permukiman.